2022
DOI: 10.1007/s10404-021-02509-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of channel height and actuation method on particle manipulation in surface acoustic wave (SAW)-driven microfluidic devices

Abstract: Surface acoustic wave (SAW) micromanipulation offers modularity, easy integration into microfluidic devices and a high degree of flexibility. A major challenge for acoustic manipulation, however, is the existence of a lower limit on the minimum particle size that can be manipulated. As particle size reduces, the drag force resulting from acoustic streaming dominates over acoustic radiation forces; reducing this threshold is key to manipulating smaller specimens. To address this, we investigate a novel excitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…Although the acoustic landscape depicted in Fig. 1 is only on the lateral plane, several numerical studies 20,31,32 showed that the relative location of the nodes, antinodes and midpoints would not vary with height. Hence, either the particle trapping locations at the bottom or at the top level shall coincide with the lateral locations of the antinodes, according to Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the acoustic landscape depicted in Fig. 1 is only on the lateral plane, several numerical studies 20,31,32 showed that the relative location of the nodes, antinodes and midpoints would not vary with height. Hence, either the particle trapping locations at the bottom or at the top level shall coincide with the lateral locations of the antinodes, according to Fig.…”
Section: Resultsmentioning
confidence: 99%
“…50 Acoustic streaming arises from the attenuation and transfer of acoustic energy into the bulk fluid flow, impacting particle motion through Stokes drag. 51,52…”
Section: Methodsmentioning
confidence: 99%
“…50 Acoustic streaming arises from the attenuation and transfer of acoustic energy into the bulk fluid flow, impacting particle motion through Stokes drag. 51,52 Whereas both acoustic radiation forces and acoustic streaming are periodic and wavelength-scale in typical acoustofluidic systems, including those driven by bulk acoustic wave (BAW) 24 and surface acoustic wave (SAW) 52,53 actuation, the use of sharp-edged microstructures here enables the generation of high streaming velocities and complex streaming vortices whose locations are determined by the local presence of these structures, rather than acoustic anti/nodal positions. Here acoustic streaming drives vortical motion around sharp tips, and the Gor'kov acoustic potential results in further particle motion in response to spatial variation in time-averaged acoustic fields, where this is calculated using a combination of the first-order pressure and velocity fields.…”
Section: Concept and Operating Principlesmentioning
confidence: 99%
“…By taking advantage of the size differences of the particles, large and small particles are subjected to greater or lesser force by the focused acoustic pressure point [ 122 ]. In acoustic separations, a pair of electrodes is slotted vertically on two sides of the microchannel, and a surface acoustic wave moves towards the microchannel [ 123 ]. Acoustic waves radiated from two opposite directions interfere with each other and generate standing waves that create pressure points at specific points depending on the wavelength inside the linear microchannel [ 124 ].…”
Section: Microfluidicsmentioning
confidence: 99%